Using Drosophila Nephrocytes to Understand the Formation and Maintenance of the Podocyte Slit Diaphragm - van de Leemput, Joyce; Wen, Pei; Han, Zhe (Frontiers in Cell and Developmental Biology, 2022)
The podocyte slit diaphragm (SD) is an essential component of the glomerular filtration barrier and its disruption is a common cause of proteinuria and many types of kidney disease. Therefore, better understanding of the pathways and proteins that play key roles in SD formation and maintenance has been of great interest. Podocyte and SD biology have been mainly studied using mouse and other vertebrate models. However, vertebrates are limited by inherent properties and technically challenging in vivo access to the podocytes. Drosophila is a relatively new alternative model system but has already made great strides. Past the initial obvious differences, mammalian podocytes and fly nephrocytes are remarkably similar at the genetic, molecular and function levels. This review discusses SD formation and maintenance, and their dependence on cell polarity, the cytoskeleton, endo- and exocytosis, as learned from studies in fly nephrocytes and mammalian podocytes. In addition, it reflects on remaining gaps in our knowledge, the physiological implications for glomerular diseases and how we can leverage the advantages Drosophila has to offer to further our understanding.